Community Resilience on Marine Tourism Destination: A Case Study at Pulau Dua, Banggai Regency - Junaid, Ilham; Salam, Nur; Maoudy, Andi Fatimah; Nurjannah, Nurjannah (Journal of Indonesian Tourism and Development Studies, 2024)
Tourism literature that explains community resilience in the context of island destinations still requires in-depth study. This research aims to 1) identify the impact of COVID-19 on marine tourism attractions; 2) analyse the determining factors for sustainable marine tourism management; 3) analyse community efforts to revive marine tourism after COVID-19. A case study approach guided the authors in understanding marine tourism and issues related to COVID-19 and community resilience in Pulau Dua, Banggai Regency (Indonesia). The authors collected research data through interviews with residents, tourism business actors, and direct observation in research areas in August 2023. The research reveals that the COVID-19 pandemic is an unexpected event and affects the sustainability of marine tourism management. COVID-19 is the primary reason for the damage to tourism facilities. There are two key factors determining the sustainability of marine tourism: COVID-19 and the successful execution of events. Tourism stakeholders should seize the opportunity presented by the post-COVID-19 period to rebuild the marine tourism sector. This research proposes strategies that tourism stakeholders can implement to enhance community resilience. The local government can enhance resilience by planning and rebuilding tourist facilities on Pulau Dua. The regional government's commitment to sustaining the success of tourism events in Pulau Dua is a testament to its resilience. Local institutional resilience is a solution to restore Pulau Dua's image as a tourism icon and marine destination.